Comparative analysis of impacted maxillary canine and dentigerous cyst diagnosis using panoramic and CBCT imaging - Muhammad Rakhmat Ersyad Muchlis; Annisa Putri; Lusi Epsilawati; Azhari Azhari (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: This report is aimed to compare diagnostic accuracy of impacted maxillary canine and dentigerous cyst in determining its dimension and position using panoramic and CBCT (cone beam computed tomography) imaging. Case Report: A 30-year-old woman was referred to Department of Dental and Maxillofacial Radiology with the suspect of upper right impacted canine. She had chief complaint of swelling pain in the palate for ± 3 months. Panoramic showed 13 impacted superiorly to the maxillary sinus and surrounding with a radiolucent lesion attached on cementoenamel junction. However, panoramic has limitations in assessing the labio-palatal position of impacted canine and lesion extension. CBCT revealed the tooth located closer to palate and no sign of direct contact with sinus. The radiolucent lesion has destructed anteroposterior aspect of cortical plate which explain the reason of swelling and pain. Conclusion: Precise dimension and position are important to avoid mistakes since impacted maxillary canine accompanied with dentigerous cyst required invasive management. In our case, panoramic and CBCT contributed to guide the diagnosis and help the referrer determining the exact site of surgery.